COMMON FIXED POINT THEOREMS FOR OCCASIONALLY WEAKLY COMPATIBLE MAPS SATISFYING PROPERTY (E. A) USING AN INEQUALITY INVOLVING QUADRATIC TERMS IN MANGER SPACE FOR SIX MAPS. (2022) - MURTHY, P. P.; PRASAD, K.N.V.V.V.; MAJUMDAR, JYOTSANA
No abstract available